Evolutionary Pseudodifferential Equations in the Spaces of Generalized Periodic Functions - Городецький, Василь Васильович; Мартинюк, Ольга Василівна (Springer, 2021)
We prove the correct solvability of the nonlocal multipoint (in time) problem for the evolutionary equation with pseudodifferential operator in the space of generalized periodic functions and an initial function, which is an element of the space of periodic ultradistributions.
Keywords: nonlocal multipoint (in time) problem, evolutionary equation, pseudodifferential operator